A quantitative characterization method for the diffusion and fusion degree of the new and old interfaces of recycled rubber asphalt

Through nano-indentation technology, the diffusion and fusion characteristics of new and old asphalt in recycled rubber asphalt are quantitatively characterized, which solves the problem of lack of accurate testing methods in the existing technology, improves the performance consistency and reliability of recycled asphalt mixtures, and supports green development.

CN118329704BActive Publication Date: 2025-03-21CHONGQING JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410467916.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2025-03-21
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

The prior art lacks accurate testing methods to characterize the diffusion fusion characteristics between new and old asphalt, resulting in large variability in the performance of recycled rubber asphalt mixtures and affecting the service performance of the pavement.

Method used

A quantitative characterization method was developed using nano-indentation technology. By preparing cylindrical-concave aggregate specimens, simulating the interface between new and old asphalts, measuring the modulus of asphalt films at different thicknesses, and calculating the degree of diffusion and depth to evaluate the diffusion behavior of new and old asphalts.

Benefits of technology

Accurate quantitative characterization of the diffusion and fusion behavior of new and old interfaces of recycled rubber asphalt is achieved, and the performance consistency and reliability of recycled asphalt mixtures are improved, and green development and resource reuse is supported.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118329704B_ABST
    Figure CN118329704B_ABST
Patent Text Reader

Abstract

The present application relates to a quantitative characterization method for the degree of fusion of diffusion characteristics of new and old interfaces of recycled rubber asphalt. The method prepares a plurality of cylindrical-concave aggregate specimens and divides them into two groups. In one group, unaged rubber asphalt is poured into the groove of the specimens and the average modulus at different thicknesses is measured as a reference value. In the other group, half of the rubber asphalt is poured and the specimens are coupled aged, sprayed with a regeneration agent, and poured with new rubber asphalt. The asphalt film modulus at different thicknesses is measured, and the diffusion fusion degree D (h) and the diffusion fusion depth h are further calculated. D , based on which the diffusion behavior of the regeneration agent at the interface between the old and new rubber asphalt is evaluated. This application prepares rubber asphalt-aggregate specimens with fixed shapes and sizes, and forms nanoindentation specimens after cutting the aged regenerated rubber asphalt specimens, which can directly test the modulus of the asphalt film at different thicknesses, avoiding secondary treatment of the aged and regenerated asphalt film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material mechanics testing and road materials, and specifically relates to a quantitative characterization method for the degree of diffusion and fusion of new and old interfaces of recycled rubber asphalt. Background Art

[0002] Most highways are mainly asphalt pavement, among which rubber asphalt pavement is widely used due to its significant advantages in reducing road noise and improving driving comfort, as well as its high cost-effectiveness, easy access to modifiers, and relatively simple process preparation. With the improvement of environmental protection standards and the emphasis on resource utilization efficiency, the recycling of old asphalt has been vigorously promoted in road engineering. At present, one of the challenges facing the field of recycled asphalt is the lack of detailed classification and evaluation mechanism for different types of old asphalt. This problem is particularly prominent in the recycling of rubber asphalt, because the performance of rubber asphalt is not only affected by the degree of aging of the asphalt, but also closely related to the quality and distribution of the rubber powder. Therefore, careful classification of old asphalt, especially distinguishing asphalt from different sources and degrees of aging, will play a key role in improving the consistency and reliability of recycled asphalt mixtures.

[0003] During the rubber asphalt regeneration process, the performance of the recycled rubber asphalt mixture shows greater variability due to the inherent differences between the asphalt and rubber powder in the raw materials, including differences in chemical composition and physical properties. This variability not only increases the difficulty of quality control of recycled materials, but also has an adverse effect on the service performance of the formed pavement. Therefore, the detailed classification of old asphalt and the dynamic characterization of the regeneration process can effectively predict the performance of the recycled rubber asphalt mixture, thereby achieving precise control of the quality of recycled asphalt.

[0004] Currently, there are few studies on the recycling process of old rubber asphalt materials, and there is a lack of accurate and systematic testing methods to characterize the diffusion and fusion characteristics between new and old asphalt. Traditional testing methods mainly use macroscopic methods, which cannot dynamically and quantitatively capture the recycling process of old asphalt materials from a microscopic scale. However, in-depth analysis of the diffusion behavior of recycled rubber asphalt at the microscopic level will help optimize its recycling process and improve the service performance of recycled asphalt pavement.

[0005] Although nanoindentation technology has been proven to be able to accurately measure the hardness and modulus of materials at the nanoscale, providing a powerful tool for revealing the microscopic properties of asphalt materials, there has been no research on its application in characterizing the diffusion and fusion characteristics of new and old components in recycled rubber asphalt, and there is also a lack of corresponding theoretical frameworks and testing procedures. Therefore, developing a method based on nanoindentation technology to accurately characterize the diffusion and fusion characteristics of new and old asphalt in recycled rubber asphalt will help further promote the sustainable reuse of rubber asphalt and support the green development of road construction. Summary of the invention

[0006] This application aims to solve the technical problem of finely characterizing the diffusion and fusion behavior of the new and old interfaces of recycled rubber asphalt raised in the aforementioned background, and proposes a quantitative characterization method for the degree of diffusion and fusion of the new and old interfaces of recycled rubber asphalt. By developing an innovative quantitative characterization method, the influence of different factors (regeneration time, regeneration temperature, regeneration agent type, regeneration agent dosage, degree of aging of old asphalt, etc.) on the diffusion and fusion characteristics of new and old components in recycled rubber asphalt is accurately described, thereby providing key material parameters for the recycling of rubber asphalt mixtures to optimize the recycling process. Quantitative characterization method for the degree of fusion of diffusion characteristics of the new and old interfaces of recycled rubber asphalt

[0007] In order to solve the above technical problems, the technical solution adopted in this application is:

[0008] A quantitative characterization method for the diffusion and fusion degree of new and old interfaces of recycled rubber asphalt, the method comprising:

[0009] Prepare a plurality of cylindrical-concave aggregate specimens, wherein the cylindrical-concave aggregate specimens include cylindrical aggregates, a groove is processed at the center of the top surface of the cylindrical aggregate, and the diameter of the groove is not less than half of the diameter of the cylindrical aggregate, and the plurality of cylindrical-concave aggregate specimens are divided into two groups, namely, group A specimens and group B specimens, each group of specimens includes m cylindrical-concave aggregate specimens, wherein m is a natural number greater than or equal to 1;

[0010] Unaged rubber asphalt was prepared as a reference group;

[0011] Preparation of aged rubber asphalt specimens;

[0012] The unaged rubber asphalt is poured into the groove of each cylindrical-concave aggregate specimen in the group A of specimens to fill the groove volume and cool it to obtain m unaged rubber asphalt-aggregate specimens with smooth surfaces as a reference group;

[0013] Pour half the volume of the rubber asphalt into the groove of each cylindrical-concave aggregate specimen in the B group of specimens and cool it to obtain m rubber asphalt-aggregate specimens;

[0014] The rubber asphalt-aggregate sample of group B is placed in an asphalt light, heat and water coupled aging test chamber for sample coupled aging, and the aging degree of the rubber asphalt is controlled by controlling the coupled aging time;

[0015] The rubber asphalt surface of the rubber asphalt-aggregate sample after the coupled aging of the sample is sprayed with a regeneration agent, and the dosage of the regeneration agent is controlled by controlling the spraying amount of the regeneration agent per unit area;

[0016] New unaged rubber asphalt is poured on the rubber asphalt-aggregate sample after spraying the regeneration agent and cooled to obtain a regenerated rubber asphalt-aggregate sample with a smooth surface;

[0017] Cutting is performed along the height direction of the asphalt film to form a nanoindentation test specimen of a set size;

[0018] Obtain the asphalt film modulus at different thicknesses of group A specimens and calculate the average modulus as a reference value;

[0019] The diffusion fusion degree D(h) and diffusion fusion depth h are calculated based on the asphalt film modulus at different thicknesses of the recycled rubber asphalt-aggregate sample. D ;

[0020] Using the diffusion fusion degree D(h) and diffusion fusion depth h D The diffusion behavior of the regeneration agent at the interface between the new and old rubber asphalt is evaluated. Further, the asphalt modulus at different thicknesses is obtained, including:

[0021] The unaged asphalt-aggregate reference group specimens of group A and the recycled rubber asphalt-aggregate specimens with smooth surfaces are frozen with liquid nitrogen, and then cut along the height direction of the asphalt film to form nanoindentation test specimens of a set size, and the bottom interface where the asphalt film contacts the aggregate is used as the first reference plane;

[0022] According to the difference between the rubber asphalt-aggregate samples of Group A and Group B, and considering the heterogeneity of the rubber asphalt material, that is, the rubber particles are mainly dispersed in the asphalt by physical mixing, and its uniformity at the microscopic scale may vary due to factors such as the distribution and size of the rubber particles and their compatibility with the matrix asphalt. This difference may lead to variability in the nanoindentation modulus test results of a single sample, so the method of calculating the average value at multiple measurement points is used to offset the local performance differences caused by the uneven distribution of rubber particles to a certain extent.

[0023] For the reference group of unaged rubber asphalt specimens in group A, six test points were selected in sequence along the height direction starting from the reference plane, namely test point 1, test point 2, test point 3, test point 4, test point 5 and test point 6; among which, the heights of test point 1, test point 2, test point 3, test point 4, test point 5 and test point 6 to the reference plane were 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm and 3mm respectively;

[0024] Nanoindentation tests were performed on the six test points of each indentation test specimen to obtain the asphalt film modulus of each test point; the asphalt film moduli of the six test points were recorded as M1, M2, M3, M4, M5 and M6, respectively.

[0025] Furthermore, the average modulus of the unaged rubber asphalt sample is calculated as the reference modulus M by the following formula: ref :

[0026]

[0027] Among them, M i is the modulus value of the ith test point, n is the total number of test points, M ref is the average modulus of the unaged rubber asphalt in the reference group.

[0028] For the recycled rubber asphalt-aggregate specimen, the rubber asphalt modulus M(h) (0≤h≤3mm) was obtained at different heights h on the cut surface of the nanoindentation test specimen, starting from the reference plane.

[0029] Furthermore, the zero diffusion depth (h0) is defined as the modulus difference between the recycled rubber asphalt and the unaged rubber asphalt in the reference group in the direction perpendicular to the asphalt film surface (M(h)-M ref ) first decreases to a predetermined threshold that is close to zero but may not be absolutely zero.

[0030] Furthermore, the diffusion fusion degree (D) of new and old asphalt is defined as the modulus value M(h) measured at depth h relative to M ref The difference ratio of the new and old asphalt diffusion fusion degree D(h) and diffusion fusion depth h D The calculation formula is as follows:

[0031]

[0032] hp=h-ho

[0033] Furthermore, the maximum diffusion fusion degree D max is the maximum value in D(h), the maximum diffusion fusion depth h max is the corresponding depth minus the zero diffusion depth (h0);

[0034] Minimum diffusion fusion degree D min is the minimum value in D(h), the minimum diffusion fusion depth h min is the corresponding depth;

[0035] Average diffusion fusion degree Where n is the number of measurement points. The average diffusion fusion depth is Dav g The corresponding depth range, rather than a single depth value.

[0036] Furthermore, m is not less than 4 and is a multiple of 4; the obtained m group B rubber asphalt-aggregate samples are divided into four groups, namely group a, group b, group c and group d;

[0037] Furthermore, the rubber asphalt-aggregate sample is placed in an asphalt light, heat, and water coupled aging test chamber for sample coupled aging, including:

[0038] The rubber asphalt-aggregate samples of group A were coupled aged in a light, heat and water coupled aging test chamber for 3 days;

[0039] The rubber asphalt-aggregate samples of group B were coupled aged in a light, heat and water coupled aging test chamber for 6 days;

[0040] The rubber asphalt-aggregate samples of group C were coupled aged in a light, heat and water coupled aging test chamber for 9 days;

[0041] The rubber asphalt-aggregate samples of group D were coupled aged in a light, heat and water coupled aging test chamber for 12 days.

[0042] Furthermore, the nanoindentation technique was used to obtain the rubber asphalt modulus M(h) (0≤h≤3mm) of groups a, b, c, and d at different heights h, and the average modulus M of each group of rubber asphalt was calculated. a 、M b 、M c 、M d ;

[0043] According to the asphalt film modulus data of each test point at 3d, 6d, 9d and 12d of coupled aging, the relationship curve between asphalt film thickness and asphalt film modulus was determined.

[0044] Furthermore, the method further comprises: establishing an estimation model of the asphalt film modulus M at the asphalt film thickness h, wherein the estimation model is expressed as:

[0045] M(h)=α0+α1h+α2h 2

[0046] Among them, α0, α1, and α2 are the estimated model coefficients, which are functions of the coupling aging time.

[0047] The estimated model coefficients α0, α1, and α2 are determined based on the relationship curve between asphalt film thickness and asphalt film modulus.

[0048] Furthermore, starting from the reference plane, each test point at the same height has three parallel test points; the three test points of each test point are subjected to nanoindentation test; and the average value of the asphalt film modulus of the three test points is taken as the asphalt film modulus of the corresponding test point.

[0049] Furthermore, each sample after coupled aging was frozen with liquid nitrogen and then cut along the height direction of the asphalt film to form an indentation test sample with four side walls all being asphalt films.

[0050] The benefits of this application are:

[0051] 1. Based on the nanoindentation micromechanical testing method, this application prepares recycled rubber asphalt-aggregate specimens with fixed shape and size. The aged recycled specimens are cut into nanoindentation specimens to directly test the modulus of the asphalt film at different thicknesses, avoiding secondary treatment of the aged and regenerated asphalt film.

[0052] 2. The present invention proposes an evaluation index D(h) for the diffusion fusion behavior of new and old asphalt in the asphalt film gradient. Compared with other methods, the method of the present invention has high repeatability, is easy to operate, and is more accurate and reliable. Therefore, the evaluation method of the present invention can more accurately and intuitively quantify the micromechanical properties of the diffusion fusion behavior of new and old asphalt of recycled rubber asphalt on the aggregate surface.

[0053] 3. During the regeneration process of recycled rubber asphalt, the modulus at different thicknesses is different due to the diffusion and fusion of new and old asphalt. The characterization method of the present invention can clarify the regeneration mechanism of recycled rubber asphalt, which is of great significance to the design of asphalt mixture materials and the recycling of waste asphalt mixtures. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a flow chart of a method for quantitatively characterizing the degree of fusion of diffusion characteristics of new and old interfaces of recycled rubber asphalt in an embodiment of the present application.

[0055] Figure 2 This is a structural diagram of a cylindrical-concave aggregate specimen according to an embodiment of the present application.

[0056] Figure 3 This is a structural diagram of an unaged rubber asphalt-aggregate reference group sample of an embodiment of the present application.

[0057] Figure 4 This is a structural diagram of pouring half of the rubber asphalt-aggregate sample in an embodiment of the present application.

[0058] Figure 5 This is a structural diagram of a rubber asphalt-aggregate sample of an embodiment of the present application that is sprayed with a regeneration agent after coupled aging.

[0059] Figure 6 This is a structural diagram of a rubber asphalt-aggregate sample after regeneration according to an embodiment of the present application. DETAILED DESCRIPTION

[0060] The following examples are only for better explanation of the present invention, but the content of the present invention is not limited to the application in the examples. Therefore, those skilled in the art can make non-essential improvements and adjustments to the implementation scheme according to the above content of the invention and apply them to other examples, which are still within the protection scope of the present invention.

[0061] The present invention will now be further described with reference to the accompanying drawings.

[0062] Embodiment 1:

[0063] The present application embodiment provides a quantitative characterization method for the degree of fusion of diffusion characteristics of the new and old interfaces of recycled rubber asphalt, such as Figure 1 As shown, it is a flow chart of the method, which is based on nanoindentation testing and specifically includes the following steps:

[0064] Step 1. Prepare cylindrical-concave aggregate specimens: select stones and process them into cylindrical aggregates with a height of not less than 1 cm; process a groove with a diameter of not less than 0.3 cm in the center of the top surface of the cylindrical aggregate to form a cylindrical-concave aggregate specimen; wherein the diameter of the groove is not less than half of the diameter of the cylindrical aggregate; the prepared cylindrical-concave aggregate specimens are divided into two groups, namely group A specimens and group B specimens; each group of specimens contains m cylindrical-concave aggregate specimens; wherein m≥1.

[0065] The structure of the prepared cylindrical-concave aggregate specimen 200 is as follows Figure 2 As shown, the cylindrical-concave aggregate specimen 200 includes a cylindrical aggregate 201 and a groove 202 opened at the center of the top surface of the cylindrical aggregate. The groove 202 is used to pour asphalt therein, and the asphalt therein is subjected to sample coupling aging, regeneration agent spraying, and pouring of new asphalt to obtain a corresponding test piece, and the specific operation will be introduced in the subsequent steps.

[0066] Exemplarily, the cylindrical aggregate has a diameter of 3.5 cm and a height of 1.5 cm; the groove has a diameter of 2.5 cm and a depth of 0.3 cm.

[0067] In a preferred embodiment, in step 1, m is not less than 4 and is a multiple of 4, for example, m=4.

[0068] Step 2, prepare rubber asphalt: heat the base asphalt to 170℃, select the rubber mesh and dosage, shear at low speed for 30 minutes, add rubber powder three times during this period. Then heat to 180℃ and shear at high speed for 60 minutes, and keep it at 150℃ for 30 minutes after shearing.

[0069] Step 3, prepare an unaged rubber asphalt-aggregate specimen reference group: pour the unaged rubber asphalt into the groove of each cylindrical-concave aggregate specimen in the group A specimens prepared in step 1 to fill the groove volume with the unaged rubber asphalt and cool it to obtain m unaged rubber asphalt-aggregate specimens with smooth surfaces as a reference group.

[0070] Step 4, prepare rubber asphalt-aggregate samples: pour half the volume of the groove of the rubber asphalt prepared in step 2 into the groove of each cylindrical-concave aggregate specimen in group B prepared in step 1, and cool it to obtain m rubber asphalt-aggregate specimens.

[0071] like Figure 3 , which is a schematic diagram of a rubber asphalt-aggregate sample 300 , wherein the rubber asphalt-aggregate sample 300 includes a cylindrical aggregate 301 , a groove 302 , and an asphalt structural layer 303 formed by pouring in the groove 302 .

[0072] In a preferred embodiment, in step 3, the obtained m unaged rubber asphalt-aggregate samples are divided into four groups, namely group a1, group b1, group c1 and group d1.

[0073] like Figure 4 , which is a schematic diagram of a rubber asphalt-aggregate sample 400 , wherein the rubber asphalt-aggregate sample 400 includes a cylindrical aggregate 401 , a groove 402 , and a rubber asphalt structural layer 403 formed by pouring in the groove 402 .

[0074] In step 4, the obtained m rubber asphalt-aggregate samples are divided into four groups, namely group a2, group b2, group c2 and group d2.

[0075] Step 5, sample coupling aging: put the rubber asphalt-aggregate samples prepared in step 4 into asphalt light, heat and water coupling aging test boxes respectively.

[0076] like Figure 5 and Figure 6 As shown, after the rubber asphalt-aggregate sample is aged by light, heat and water coupling for different lengths in step 5, the regeneration agent 501 is sprayed on the aged rubber asphalt surface 502, and the dosage of the regeneration agent is controlled by controlling the spraying amount of the regeneration agent per unit area.

[0077] In a preferred embodiment, in the coupled aging of step 5, the aging method is as follows:

[0078] The rubber asphalt-aggregate samples of group A2 were coupled aged for 3 days in a light, heat and water coupled aging test chamber.

[0079] The rubber asphalt-aggregate samples of group B2 were coupled aged in a light, heat and water coupled aging test chamber for 6 days.

[0080] The rubber asphalt-aggregate samples of group C2 were coupled aged in a light, heat and water coupled aging test chamber for 9 days.

[0081] The rubber asphalt-aggregate samples of group d2 were coupled aged in a light, heat and water coupled aging test chamber for 12 days.

[0082] Step 6: After the rubber asphalt-aggregate sample prepared in step 5 is coupled and aged, a certain amount of regeneration agent is sprayed on the surface of the aged asphalt.

[0083] Step 7: Pour new base asphalt on the rubber asphalt-aggregate sample prepared in step 6 and cool it to obtain a regenerated rubber asphalt-aggregate sample with a smooth surface.

[0084] In a preferred embodiment, in step 3 and step 7, after the rubber asphalt is poured in the groove, it is cooled to room temperature, and then a hot scraper is used to scrape the rubber asphalt and the aggregate surface flat.

[0085] This application proposes for the first time the diffusion fusion degree D(h) and diffusion fusion depth h calculated by nanoindentation test. D As an evaluation index of the diffusion behavior of new and old asphalt, compared with other methods, this application has high repeatability, simple operation, and is more accurate and reliable. It can more accurately and intuitively characterize the micromechanical properties of the diffusion behavior of new and old asphalt of recycled rubber asphalt on the aggregate surface. Parameters Diffusion degree D (h) and diffusion fusion depth h D The calculation method of will be explained in detail in the subsequent steps.

[0086] Taking the recycled rubber asphalt-aggregate sample as an example, the sample structure obtained by step 7 is as follows: Figure 6 As shown, the recycled rubber asphalt-aggregate sample 600 includes a cylindrical aggregate 601, a groove 602, a rubber asphalt structural layer 603 formed by pouring in the groove 302, a newly poured rubber asphalt structural layer 605, and a regenerant membrane 604 located between the rubber asphalt structural layer 603 and the newly poured rubber asphalt structural layer 605.

[0087] Step 8: Obtain the asphalt film modulus at different thicknesses. The specific obtaining method includes the following steps:

[0088] Step 8A, sample cutting: Each sample after regeneration in step 7 is frozen with liquid nitrogen and cut along the height direction of the asphalt film to form an indentation test sample of a set size, and the bottom interface where the asphalt film contacts the aggregate is used as the reference plane.

[0089] In a preferred embodiment, in step 8A, each sample that has not been aged in step 3 and has been coupled aged in step 7 is placed in liquid nitrogen for freezing and storage for 0.5 h, and then cut along the height direction of the asphalt film to form an indentation test sample with a side length of 1.5 cm and four side walls that are all asphalt films.

[0090] Step 8B, asphalt film thickness marking: on the cut surface of the indentation test specimen, starting from the reference plane, select six test points in sequence along the height direction, namely test point 1, test point 2, test point 3, test point 4, test point 5 and test point 6; among which, the heights of test point 1, test point 2, test point 3, test point 4, test point 5 and test point 6 to the reference plane are 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm and 3mm respectively.

[0091] In a preferred embodiment, in step 8B, starting from the reference plane, each test point at the same height has three parallel test points.

[0092] Step 8C, nanoindentation test: perform nanoindentation test on the six test points of each indentation test sample, and then obtain the asphalt film modulus of each test point; wherein the asphalt film modulus of the six test points is respectively recorded as M 0.5 , M1, M 1.5 , M2, M 2.5 and M3.

[0093] In a preferred embodiment, in step 8C, nanoindentation tests are performed on three test points of each test point; and the average value of the asphalt film modulus of the three test points is taken as the asphalt film modulus of the corresponding test point.

[0094] In a preferred embodiment, in step 8, the asphalt film modulus data of each test point at 3d, 6d, 9d and 12d of coupled aging can be obtained; then a relationship curve between the asphalt film thickness and the asphalt film modulus at different coupled aging times is plotted.

[0095] For example, the nanoindentation technique is used to obtain the rubber asphalt modulus M(h) (0≤h≤3mm) of groups a, b, c, and d at different heights h, and the average modulus value M of each group of rubber asphalt is calculated. a 、M b 、M c 、M d ; According to the asphalt film modulus data of each test point at 3d, 6d, 9d and 12d of coupled aging, the relationship curve between asphalt film thickness and asphalt film modulus is determined.

[0096] Step 9: Calculate the average modulus of the unaged rubber asphalt sample as the reference modulus M using the following formula: ref :

[0097]

[0098] Among them, M i is the modulus value of the ith test point, n is the total number of test points, M ref is the average modulus of the unaged rubber asphalt in the reference group;

[0099] For the recycled rubber asphalt-aggregate specimens, the rubber asphalt modulus M(h) was obtained at different heights h on the cut surface of the nanoindentation test specimen, starting from the reference plane, using nanoindentation technology, where 0≤h≤3mm.

[0100] The zero diffusion depth h0 is defined as the depth value corresponding to the time when the modulus difference between the recycled rubber asphalt and the unaged rubber asphalt of the reference group first decreases to a predetermined threshold value that is close to zero but not absolutely zero in the direction perpendicular to the asphalt film surface;

[0101] The diffusion fusion degree D of new and old asphalt is defined as the modulus value M(h) measured at depth h relative to M ref The difference ratio of the new and old asphalt diffusion fusion degree D(h) and diffusion fusion depth h D The calculation formula is as follows:

[0102]

[0103] h D =h-h0

[0104] Maximum diffusion fusion degree D max is the maximum value in D(h), the maximum diffusion fusion depth h max is the corresponding depth minus the zero diffusion depth (h0);

[0105] Minimum diffusion fusion degree D min is the minimum value in D(h), the minimum diffusion fusion depth h min is the corresponding depth;

[0106] The average diffusion fusion degree is expressed as Where n is the number of measurement points, and the average diffusion fusion depth is D avg The corresponding depth range.

[0107] That is, this embodiment can also evaluate the diffusion behavior of the regeneration agent at the interface between new and old rubber asphalt by averaging the degree of diffusion fusion.

[0108] Step 10: Establish an estimation model for the asphalt film modulus M at the asphalt film thickness h, as shown below:

[0109] M(h)=α0+α1h+α2h 2

[0110] Among them, α0, α1, and α2 are estimated model coefficients, which are functions of the coupled aging time t. The estimated model coefficients α0, α1, and α2 are determined according to the relationship curve between the asphalt film thickness and the asphalt film modulus.

[0111] Embodiment 2:

[0112] The present application embodiment provides a specific example of a method for quantitatively characterizing the degree of fusion of diffusion characteristics of the new and old interfaces of recycled rubber asphalt. The example can be as follows: Figure 1 The process shown is executed.

[0113] Specifically, for the reference group of unaged rubber asphalt samples in group A, the asphalt film moduli at the six test points were M1 = 61.25 MPa, M2 = 61.26 MPa, M3 = 61.24 MPa, M4 = 61.25 MPa, M5 = 61.24 MPa and M6 = 61.24 MPa, respectively. The average modulus of unaged rubber asphalt is:

[0114]

[0115] After aging for 3 days, the heights of 6 measuring points to the reference plane of group B were 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm and 3mm respectively, and the modulus was:

[0116] M(0.5)=67.56MPa, M(1)=65.67MPa, M(1.5)=64.72MPa, M(2)=63.38MPa, M(2.5)=62.59MPa, M(3)=61.30MPa.

[0117] Zero diffusion depth h0 = 3 mm, diffusion fusion degree D(h) at 1.5 mm and diffusion fusion depth h D for:

[0118]

[0119] h D =h-h0=1.5-3=-1.5mm

[0120] Maximum diffusion fusion degree:

[0121]

[0122] Maximum diffusion fusion depth:

[0123] h max =0.5-h0=0.5-3=-2.5mm

[0124] Minimum diffusion fusion degree:

[0125]

[0126] Minimum diffusion fusion depth:

[0127] h min =3mm

[0128] Average diffusion fusion degree:

[0129]

[0130] Estimation model for calculating the asphalt film modulus M at the asphalt film thickness h: M(h) = α0 + α1h + α2h 2

[0131] Calculate α0, α1, α2:

[0132] When h = 0.5, M(0.5) = 67.56 MPa;

[0133] When h = 1, M(1) = 65.67 MPa;

[0134] When h = 1.5, M(1.5) = 64.72 MPa;

[0135] When h = 2, M(2) = 63.38 MPa;

[0136] When h = 2.5, M(2.5) = 62.59 MPa;

[0137] When h=3, M(3)=61.30MPa.

[0138] Substituting into the estimation model, we get the following equations:

[0139] α0+0.5α1+0.25α2=67.56;

[0140] α0+α1+α2=65.67;

[0141] α0+1.5α1+2.25α2=64.72;

[0142] α0+2α1+4α2=63.38;

[0143] α0+2.5α1+6.25α2=62.59;

[0144] α0+3α1+9α2=61.30.

[0145] The results of the least squares calculation using Excel are as follows:

[0146] α0=68.998, α1=-3.3031, α2=0.26.

[0147] The estimated model is: M(h) = 68.998-3.3031h+0.26h 2 .

[0148] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and should all be included in the scope of the claims and specification of the present invention.

Claims

1. A quantitative characterization method for the fusion degree of diffusion characteristics of the new and old interfaces of recycled rubber asphalt, characterized in that: The method comprises: Prepare a plurality of cylindrical-concave aggregate specimens, wherein the cylindrical-concave aggregate specimens include cylindrical aggregates, a groove is processed at the center of the top surface of the cylindrical aggregate, and the diameter of the groove is not less than half of the diameter of the cylindrical aggregate, and the plurality of cylindrical-concave aggregate specimens are divided into two groups, namely, group A specimens and group B specimens, each group of specimens includes m cylindrical-concave aggregate specimens, wherein m is a natural number greater than or equal to 1; Unaged rubber asphalt was prepared as a reference group; Preparation of aged rubber asphalt specimens; The unaged rubber asphalt is poured into the groove of each cylindrical-concave aggregate specimen in the group A of specimens to fill the groove volume and cool it to obtain m unaged rubber asphalt-aggregate specimens with smooth surfaces as a reference group; Pour half the volume of the rubber asphalt into the groove of each cylindrical-concave aggregate specimen in the B group of specimens and cool it to obtain m rubber asphalt-aggregate specimens; The rubber asphalt-aggregate sample of group B is placed in an asphalt light, heat and water coupled aging test chamber for sample coupled aging, and the aging degree of the rubber asphalt is controlled by controlling the coupled aging time; The rubber asphalt surface of the rubber asphalt-aggregate sample after the coupled aging of the sample is sprayed with a regeneration agent, and the dosage of the regeneration agent is controlled by controlling the spraying amount of the regeneration agent per unit area; New unaged rubber asphalt is poured on the rubber asphalt-aggregate sample after spraying the regeneration agent and cooled to obtain a regenerated rubber asphalt-aggregate sample with a smooth surface; Cutting is performed along the height direction of the asphalt film to form a nanoindentation test specimen of a set size; Obtain the asphalt film modulus at different thicknesses of group A specimens and calculate the average modulus as a reference value; The diffusion fusion degree D(h) and diffusion fusion depth h are calculated based on the asphalt film modulus at different thicknesses of the recycled rubber asphalt-aggregate sample. D ; Using the diffusion fusion degree D(h) and diffusion fusion depth h D To evaluate the diffusion behavior of the rejuvenating agent at the interface between the new and old rubber asphalt; For the recycled rubber asphalt-aggregate specimens, the rubber asphalt modulus M(h) was obtained at different heights h using nanoindentation technology starting from the reference plane on the cut surface of the nanoindentation test specimen, where 0≤h≤3mm; The zero diffusion depth h0 is defined as the depth value corresponding to the time when the modulus difference between the recycled rubber asphalt and the unaged rubber asphalt of the reference group first decreases to a predetermined threshold value that is close to zero but not absolutely zero in the direction perpendicular to the asphalt film surface; The average modulus of the unaged rubber asphalt sample is calculated as the reference modulus M by the following formula: ref : Among them, M i is the modulus value of the ith test point, n is the total number of test points, M ref is the average modulus of the unaged rubber asphalt in the reference group; The degree of diffusion and fusion of new and old asphalt D is defined as the modulus value M(h) measured at depth h relative to the reference modulus M ref The difference ratio of the new and old asphalt diffusion fusion degree D(h) and diffusion fusion depth h D The calculation formula is as follows: h D =h-h0。 2. The method according to claim 1, characterized in that The asphalt modulus at different thicknesses is obtained by the following method: The unaged asphalt-aggregate reference group specimens of group A and the recycled rubber asphalt-aggregate specimens with smooth surfaces are frozen with liquid nitrogen, and then cut along the height direction of the asphalt film to form nanoindentation test specimens of a set size, and the bottom interface where the asphalt film contacts the aggregate is used as the first reference plane; According to the difference between the rubber asphalt-aggregate samples of group A and group B, and considering the heterogeneity of the rubber asphalt material, that is, the rubber particles are mainly dispersed in the asphalt by physical mixing, and its uniformity at the microscopic scale will vary due to the distribution, size and compatibility of the rubber particles with the matrix asphalt. This difference leads to variability in the nanoindentation modulus test results of a single sample. Therefore, the method of calculating the average value at multiple measuring points is used to offset the local performance differences caused by the uneven distribution of rubber particles to a certain extent. For the reference group of unaged rubber asphalt specimens in group A, six test points were selected in sequence along the height direction starting from the reference plane, namely test point 1, test point 2, test point 3, test point 4, test point 5 and test point 6; among which, the heights of test point 1, test point 2, test point 3, test point 4, test point 5 and test point 6 to the reference plane were 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm and 3mm respectively; Nanoindentation tests were performed on six test points of each indentation test specimen to obtain the asphalt film modulus of each test point; the asphalt film moduli of the six test points were recorded as M1, M2, M3, M4, M5 and M6, respectively.

3. The method according to claim 1, characterized in that Maximum diffusion fusion degree D max is the maximum value in D(h), the maximum diffusion fusion depth h max is the corresponding depth minus the zero diffusion depth (h0); Minimum diffusion fusion degree D min is the minimum value in D(h), the minimum diffusion fusion depth h min is the corresponding depth; The average diffusion fusion degree is expressed as Where n is the number of measurement points, and the average diffusion fusion depth is D avg The corresponding depth range.

4. The method according to claim 1, characterized in that: m is not less than 4 and is a multiple of 4; the obtained m group B rubber asphalt-aggregate samples are divided into four groups, namely group a, group b, group c and group d.

5. The method according to claim 4, characterized in that The rubber asphalt-aggregate sample is placed in an asphalt light, heat and water coupled aging test chamber for sample coupled aging, including: The rubber asphalt-aggregate samples of group A were coupled aged in a light, heat and water coupled aging test chamber for 3 days; The rubber asphalt-aggregate samples of group B were coupled aged in a light, heat and water coupled aging test chamber for 6 days; The rubber asphalt-aggregate samples of group C were coupled aged in a light, heat and water coupled aging test chamber for 9 days; The rubber asphalt-aggregate samples of group D were coupled aged in a light, heat and water coupled aging test chamber for 12 days.

6. The method according to claim 5, characterized in that The nanoindentation technique was used to obtain the rubber asphalt modulus M(h) (0≤h≤3mm) of groups a, b, c, and d at different heights h, and the average modulus M of each group of rubber asphalt was calculated. a 、M b 、M c 、M d ; According to the asphalt film modulus data of each test point at 3d, 6d, 9d and 12d of coupled aging, the relationship curve between asphalt film thickness and asphalt film modulus was determined.

7. The method according to claim 6, characterized in that The method further includes: establishing an estimation model of the asphalt film modulus M at the asphalt film thickness h, wherein the estimation model is expressed as: M(h)=α0+α1h+α2h 2 Among them, α0, α1, and α2 are the estimated model coefficients, which are functions of the coupling aging time. The estimated model coefficients α0, α1, and α2 are determined based on the relationship curve between asphalt film thickness and asphalt film modulus.

8. The method according to claim 2, characterized in that: Starting from the reference plane, each test point at the same height has three parallel test points; the three test points of each test point are subjected to nanoindentation test; the average value of the asphalt film modulus of the three test points is taken as the asphalt film modulus of the corresponding test point.

9. The method according to claim 1, characterized in that: Each sample after coupled aging was frozen with liquid nitrogen and then cut along the height direction of the asphalt film to form an indentation test sample with four side walls all covered with asphalt film.

Citation Information

Patent Citations

  • Asphalt film gradient aging characteristic characterization method based on nanoindentation test

    CN114397211A

  • Pavement repair system

    WO2014151973A1